Associations of chest X-ray trajectories, smoking, and the risk of lung cancer in two population-based cohort studies - Liu, Ya; Feng, Zhuowei; Fan, Zeyu; Zhang, Yu; Li, Chenyang; Liu, Xiaomin; Duan, Hongyuan; Cui, Xiaonan; Zhang, Liwen; Sheng, Chao; Yang, Lei; Gao, Ying; et al. (Frontiers in Oncology, 2023)
Objectives: Despite increasing use of computed tomography (CT), chest X-ray (CXR) remains the first-line investigation for suspected lung cancer (LC) in primary care. However, the associations of CXR trajectories, smoking and LC risk remain unknown.Methods: A total of 52,486 participants from the PLCO and 22,194 participants from the NLST were included. The associations of CXR trajectories with LC risk were evaluated with multivariable COX regression models and pooled with meta-analyses. Further analyses were conducted to explore the stratified associations by smoking status and the factors associated with progression and regression in CXR.Results: Compared to stable negative CXR (CXRSN), HRs(95%CIs) of LC incidence were 2.88(1.50-5.52), 3.86(2.03-7.35), and 1.08(0.80-1.46) for gain of positive CXR (CXRGP), stable positive CXR (CXRSP), and loss of positive CXR (CXRLP), while risk of LC mortality were 1. 58(1.33-1.87), 2.56(1.53-4.29), and 1.05(0.89-1.25). Similar trends were observed across different smoking status.However, LC risk with CXRGP overweighed that with CXRSP among ever smokers [2.